Challenges in diagnosing Autism Spectrum Disorder in childhood (Research, Society and Development, 2023)
Introduction: Autism spectrum disorder (ASD) is a biologically based neurodevelopmental disorder characterized by persistent deficits in communication and social interaction and restricted and repetitive patterns of behavior, interests and activities. It is one of the most challenging neurodevelopmental diagnoses in children today. The literature includes prevalence studies from around the world, but only three meta-analyses are found. Objective: analyze, describe and classify data, with the aim of gathering knowledge about the relevance of the diagnosis and early therapeutic approach to autism, to improve the prognosis and quality of life of patients. Methods: this is an integrative literature review. The search began by creating the basic question and selecting the descriptors “Clinical Diagnosis”; “Autism Spectrum Disorder”; “Child”, in the Decs/Mesh thesaurus, and were used in the Scielo, UpToDate, Pubmed and regional portal VHL databases using “TEA” and “ASD diagnosis in pediatrics” as the search strategy. Results: articles that presented data related to Autism Spectrum Disorder were analyzed and it was identified that 19 productions addressed the central theme. Conclusions: the later the diagnosis of the syndrome, the worse its prognosis and lifestyle adjustment.